Multi-layer structure cable with high thermal conductivity
By using modified thermally conductive carbon fibers, a tight carbon fiber network structure is formed, which solves the problem of insufficient thermal conductivity of existing cable sheaths, significantly improves the thermal conductivity, and ensures efficient heat dissipation and long life of the cable.
Patent Information
- Application Number
- CN202411736901.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
The thermal conductivity of the thermal conductivity in the existing cable sheath is insufficient, resulting in limited thermal conductivity, affecting the thermal conductivity of the cable.
Modified thermally conductive carbon fibers are used to improve the surfactivity and crosslinking degree of thermally conductive carbon fibers through hydrogen peroxide treatment, silane coupling agent graft modification and crosslinking agent adsorption modification, and form a tight carbon fiber network structure. The carbon fiber network structure is tightly wrapped in the outer sheath layer of the cable, enhancing the heat conduction effect.
Through the use of modified thermally conductive carbon fibers, the thermal conductivity of the cable sheath layer is significantly improved, ensuring rapid and effective heat transmission, extending the service life of the cable and improving the efficiency of power transmission.
Smart Images

Figure CN119626655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of power supply cable design and processing, and in particular relates to a multi-layer structure cable with high thermal conductivity. Background Art
[0002] The cable will generate heat during the power transmission process, causing the temperature of the cable core to rise. If the thermal conductivity of the sheath used to wrap the core is too poor, it will be difficult to dissipate the heat in time, which will cause the temperature of the core wire inside the cable to further increase, thereby reducing the current carrying capacity of the cable core and affecting the normal transmission of electricity.
[0003] In order to improve thermal conductivity and promote heat dissipation, some thermal conductive materials are usually added to the jacket. Thermal conductive materials are usually inorganic materials, such as carbon fiber, etc. And in order to further improve the dispersion uniformity of these inorganic thermal conductive materials in the resin jacket, the inorganic thermal conductive materials will be subjected to certain surface treatment modifications before adding. Although this surface treatment modification retains the mechanical properties of the jacket coating to a certain extent by promoting dispersion, it is still relatively limited in helping the thermal conductivity itself.
[0004] In this regard, the applicant believes that this is because after promoting dispersion, although the agglomeration of fibers is reduced, the connection between fibers will also become weaker. Assuming that a thermally conductive carbon fiber has no contact with other fibers, even if heat is transferred to this thermally conductive carbon fiber, it is surrounded by the organic matrix with poor thermal conductivity of the sheath, and no other carbon fibers are in contact with it, resulting in the heat on this thermally conductive carbon fiber cannot be transferred away in a timely and effective manner. From a macroscopic point of view, it will inevitably affect the thermal conduction and heat dissipation effect of the entire sheath coating. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a multi-layer structure cable with high thermal conductivity, comprising an insulated shielded wire core, wherein the insulated shielded wire core comprises a conductor wire core, an insulating layer tightly wrapped outside the conductor wire core, and a shielding layer tightly wrapped outside the insulating layer; the cable also comprises an outer sheath layer tightly wrapped outside the insulated shielded wire core,
[0006] Wherein, modified thermally conductive carbon fibers are dispersedly doped in the outer sheath layer.
[0007] Preferably, the conductor core is formed by twisting a plurality of round copper wires.
[0008] Preferably, the shielding layer is a wire mesh woven from copper wires.
[0009] Preferably, the outer sheath layer comprises, by weight, 100 parts of polypropylene, 5-20 parts of POE thermoplastic elastomer, 1-3 parts of modified thermal conductive carbon fiber, 2-3 parts of plasticizer, 0.5-1.5 parts of antioxidant, and 0.3-1 part of lubricant.
[0010] Further: the modified thermally conductive carbon fiber is a thermally conductive carbon fiber that has been modified by grafting with a reactive silane coupling agent and adsorbing with a crosslinking agent in sequence, and the specific modification method is:
[0011] (1) At room temperature (25°C, the same below), the thermal conductive carbon fiber is immersed in a hydrogen peroxide aqueous solution with a mass concentration of 3% to 5% for 1 to 5 hours according to a material-liquid ratio of 1:50 to 1:10 to achieve surface oxidation treatment of the thermal conductive carbon fiber.
[0012] (2) At room temperature, according to a material-liquid ratio of 1:30 to 1:10, the thermally conductive carbon fiber subjected to surface oxidation treatment in step (1) is immersed in a dispersion of a reactive silane coupling agent having a mass concentration of 0.5% to 1.5% for 0.5 to 1.5 hours to achieve surface grafting modification of the thermally conductive carbon fiber.
[0013] Among them, the reactive silane coupling agent has a carbon-carbon double bond in its molecular structure, such as KH570, etc. The solvent of the reactive silane coupling agent dispersion is ethanol and water mixed in a mass ratio of 8 to 10:1.
[0014] (3) At room temperature, according to a material-liquid ratio of 1:15 to 1:10, the thermal conductive carbon fiber surface-grafted in step (2) is immersed in a cross-linking agent dispersion having a mass concentration of 1% to 5% for 2 to 4 hours to achieve cross-linking agent adsorption modification of the thermal conductive carbon fiber.
[0015] Wherein, the crosslinking agent is an organic peroxide, such as dicumyl peroxide, dibenzoyl peroxide, etc., and the solvent of the crosslinking agent dispersion is volatile acetone.
[0016] Furthermore: the antioxidant is antioxidant 1010 or antioxidant 168.
[0017] Furthermore: the plasticizer is dioctyl phthalate.
[0018] Furthermore: the lubricant is zinc stearate, calcium stearate or silicone powder.
[0019] Preferably, the cable processing method comprises: melting the insulating layer masterbatch in an extruder, extruding it on the outer surface of the conductor core, and forming an insulating layer tightly covering the conductor core after cooling; weaving a shielding layer on the outer surface of the insulating layer; melting the masterbatch for preparing the outer sheath layer in an extruder, extruding it on the surface of the insulating shielding core, and forming an outer sheath layer tightly covering the insulating shielding core after cooling.
[0020] The beneficial effects of the present invention are as follows: the organic resin sheath coating of the conductor core is filled with carbon fiber whose thermal conductivity is improved after modification, thereby improving the thermal conduction effect of the sheath coating; at the same time, the insulating layer and the outer sheath layer are formed by directly extruding the resin mixture on the inner layer surface after melting and then cooling, thereby effectively ensuring the contact tightness between the layers (wherein, since the shielding layer between the insulating layer and the outer sheath layer is a network woven from copper wires, the outer sheath layer extruded on the shielding layer will partially pass through the mesh on the shielding layer while hot, and further contact and combine with the inner insulating layer), ensuring the continuity of heat conduction.
[0021] The modified thermally conductive carbon fibers are first treated with hydrogen peroxide to enrich the functional groups on the surface of the thermally conductive carbon fibers, so that more silane coupling agents can be stably bonded to the surface of the thermally conductive carbon fibers; these grafted silane coupling agents carry carbon-carbon double bonds; during the extrusion process, the free radicals generated by the thermal decomposition of the cross-linking agent added to the mixture to achieve micro-cross-linking between matrix polymers (polypropylene, etc.) can also initiate polymerization between these carbon-carbon double bonds. If different thermally conductive carbon fibers can be chemically connected together through the polymerization reaction, the contact between the local sections of the single carbon fiber and the carbon fiber in the thermally conductive carbon fiber network structure formed in the matrix of the sheath coating layer will be closer, so the heat falling on a certain carbon fiber will be quickly conducted away through the other carbon fibers in contact with it, and so on, so that the sheath coating layer penetrated by the carbon fiber network can show a more ideal heat conduction effect.
[0022] It can be seen that the crosslinking agent is also one of the key factors to promote the reaction and connection of carbon-carbon double bonds. However, if the conventional addition method is followed (such as in Comparative Example 2, the thermal conductive carbon fiber modified by the silane coupling agent, the crosslinking agent and the matrix polymer, and other additives are directly and simply blended and added to the extruder), the thermal conductive carbon fiber and the crosslinking agent are independently dispersed in the mixed system, and the crosslinking agent is more surrounded by the polypropylene matrix. The free radicals converted by heat are more likely to induce micro-crosslinking between polypropylene macromolecular chains or grafting between polypropylene macromolecular chains and carbon-carbon double bonds on carbon fibers. There are very few of these crosslinking agents that can actually induce the addition of carbon-carbon double bonds on two different carbon fibers together. Therefore, it is impossible to effectively form the desired state of "in the thermal conductive carbon fiber network structure, a single carbon fiber and a carbon fiber (local segment) are directly chemically connected and in close contact" in the previous paragraph. If the amount of crosslinking agent is blindly increased, the mechanical properties of the processed sheath coating will have a significant adverse effect.
[0023] To this end, this solution mainly utilizes the physical adsorption of micropores on the thermally conductive carbon fiber. The required amount of cross-linking agent is first concentratedly adsorbed for a certain period of time, and then the carbon fiber and the base resin are added to the extruder together. Since the loading of the cross-linking agent is a physical adsorption, a large part of the cross-linking agent adsorbed on the fiber will be separated from the fiber again and dispersed into the resin base material under the action of the temperature rise and shear of extrusion. Therefore, it can also effectively induce micro-cross-linking between polypropylene macromolecular chains or grafting connection between polypropylene macromolecular chains and carbon-carbon double bonds on carbon fibers, ensuring the mechanical properties of the processed coating layer; more importantly, a part of the cross-linking agent that has not been separated from the carbon fiber is directly converted into free radicals on the carbon fiber after heating, which is equivalent to giving the carbon fiber where it is located free radical activity. On the one hand, the free radical can indeed attack the double bonds around it to initiate polymerization. On the other hand, there is also a strong quenching tendency between free radicals. This quenching tendency enhances the mutual attraction (local segments) between two different carbon fibers with free radical activity, thereby greatly increasing the probability of the carbon-carbon double bonds (of the silane coupling agent) on the two carbon fibers to directly react and add together, thereby realizing the chemical connection contact of the local segments between the two carbon fibers. On a macro level, the contact between individual carbon fibers in the thermally conductive carbon fiber network that runs through the sheath coating becomes closer, making the heat conduction of the entire thermally conductive carbon fiber network faster and more effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the internal layer structure of the multi-layer structure cable with high thermal conductivity of the present invention (cut in cross section), wherein 1 is an insulating shielding core, 11 is a conductor core, 12 is an insulating layer, 13 is a shielding layer, and 2 is an outer sheath layer. DETAILED DESCRIPTION
[0025] Example 1
[0026] Modification of thermal conductive carbon fiber:
[0027] (1) At room temperature, according to a material-liquid ratio of 1:20, a thermal conductive carbon fiber (diameter of about 8 μm, length of about 4 mm, the same below) is immersed in a 5% mass concentration hydrogen peroxide aqueous solution for 4 hours, and then the thermal conductive carbon fiber is taken out and naturally air-dried, thereby completing the surface oxidation treatment of the thermal conductive carbon fiber;
[0028] (2) At room temperature, according to a material-liquid ratio of 1:15, the thermally conductive carbon fiber subjected to surface oxidation treatment in step (1) is immersed in a KH570 dispersion (obtained by dispersing KH570 in a solvent prepared by mixing ethanol and water in a mass ratio of 9:1 according to a mass concentration of KH570 of 1.5%, the same below) for 1 hour, and then the thermally conductive carbon fiber is taken out and naturally air-dried, thereby completing the surface grafting modification of the thermally conductive carbon fiber;
[0029] (3) At room temperature, according to a material-liquid ratio of 1:15, the thermally conductive carbon fiber surface-grafted in step (2) is sealed and immersed in an acetone dispersion of diisopropylbenzene peroxide with a mass concentration of 3% for 4 hours, and then the thermally conductive carbon fiber is taken out and naturally air-dried until the solvent acetone evaporates naturally, thus completing the cross-linking agent adsorption modification of the thermally conductive carbon fiber to obtain a modified thermally conductive carbon fiber.
[0030] Processing and preparation of outer sheath layer masterbatch:
[0031] Calculated by weight, 100 parts of polypropylene (Yanshan Petrochemical 1396D, the same below), 10 parts of POE thermoplastic elastomer (Dow 8480, the same below), 2.5 parts of modified thermal conductive carbon fiber prepared in this embodiment, 2 parts of dioctyl phthalate, 0.5 parts of antioxidant 1010, and 0.5 parts of zinc stearate are added together into a high-speed mixer and blended at a speed of 1200r / min for 10min to obtain a mixture; the obtained mixture is blended, extruded and granulated through a screw extruder at 170°C to 200°C to serve as a masterbatch for the outer sheath layer.
[0032] Cable preparation:
[0033] After conventional insulation layer masterbatch is melted in an extruder, it is extruded on the outer surface of the conductor core, and after cooling, an insulation layer tightly wrapped on the conductor core is formed; a shielding layer is woven on the outer surface of the insulation layer; the outer sheath layer masterbatch prepared in this embodiment is melted and extruded on the surface of the insulation shielding core at 170℃~200℃ in an extruder, and after cooling, an outer sheath layer tightly wrapped around the insulation shielding core is formed (the thickness of the outer sheath layer is 1.8mm, the same below). The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.
[0034] Example 2
[0035] Processing and preparation of outer sheath layer masterbatch:
[0036] Calculated by weight, 100 parts of polypropylene, 13 parts of POE thermoplastic elastomer, 3 parts of modified thermal conductive carbon fiber prepared in Example 1, 2 parts of dioctyl phthalate, 0.8 parts of antioxidant 1010, and 0.5 parts of calcium stearate are added together into a high-speed mixer and blended at a speed of 1200r / min for 15min to obtain a mixture; the obtained mixture is blended, extruded, and granulated through a screw extruder at 170°C to 200°C to serve as a masterbatch for the outer sheath layer.
[0037] Cable preparation:
[0038] After conventional insulation layer masterbatch is melted in an extruder, it is extruded on the outer surface of the conductor core, and after cooling, an insulation layer tightly wrapped on the conductor core is formed; a shielding layer is woven on the outer surface of the insulation layer; the outer sheath layer masterbatch prepared in this embodiment is melted and extruded on the surface of the insulation shielding core in an extruder at 170℃~200℃, and after cooling, an outer sheath layer tightly wrapped around the insulation shielding core is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.
[0039] Example 3
[0040] Processing and preparation of outer sheath layer masterbatch:
[0041] Calculated by weight, 100 parts of polypropylene, 8 parts of POE thermoplastic elastomer, 2 parts of modified thermal conductive carbon fiber prepared in Example 1, 3 parts of dioctyl phthalate, 1 part of antioxidant 1010, and 0.8 parts of zinc stearate are added together into a high-speed mixer and blended at a speed of 1500r / min for 10 minutes to obtain a mixture; the obtained mixture is blended, extruded, and granulated through a screw extruder at 170°C to 200°C to serve as a masterbatch for the outer sheath layer.
[0042] Cable preparation:
[0043] After conventional insulation layer masterbatch is melted in an extruder, it is extruded on the outer surface of the conductor core, and after cooling, an insulation layer tightly wrapped on the conductor core is formed; a shielding layer is woven on the outer surface of the insulation layer; the outer sheath layer masterbatch prepared in this embodiment is melted and extruded on the surface of the insulation shielding core in an extruder at 170℃~200℃, and after cooling, an outer sheath layer tightly wrapped around the insulation shielding core is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.
[0044] Comparative Example 1
[0045] Modification of thermal conductive carbon fiber:
[0046] The silane coupling agent KH570 was replaced with an equal molar amount of "isobutyltrimethoxysilane", and the rest of the operations were the same as in Example 1:
[0047] (1) Same as step (1) of Example 1;
[0048] (2) At room temperature, according to a material-liquid ratio of 1:15, the thermally conductive carbon fiber subjected to surface oxidation treatment in step (1) of this comparative example was immersed in an isobutyl trimethoxy silane dispersion (obtained by dispersing isobutyl trimethoxy silane in a solvent prepared by mixing ethanol and water in a mass ratio of 9:1 according to a mass concentration of isobutyl trimethoxy silane of 1.1%) for 1 hour, and then the thermally conductive carbon fiber was taken out and naturally air-dried, thereby completing the surface grafting modification of the thermally conductive carbon fiber;
[0049] (3) At room temperature, according to a material-liquid ratio of 1:15, the thermally conductive carbon fiber surface-grafted modified in step (2) of this comparative example is sealed and immersed in an acetone dispersion of diisopropylbenzene peroxide with a mass concentration of 3% for 4 hours, and then the thermally conductive carbon fiber is taken out and naturally air-dried until the solvent acetone is fully volatilized, thus completing the cross-linking agent adsorption modification of the thermally conductive carbon fiber to obtain a modified thermally conductive carbon fiber.
[0050] Processing and preparation of outer sheath layer masterbatch:
[0051] Calculated by weight, 100 parts of polypropylene, 10 parts of POE thermoplastic elastomer, 2.5 parts of modified thermal conductive carbon fiber prepared in this comparative example, 2 parts of dioctyl phthalate, 0.5 parts of antioxidant 1010, and 0.5 parts of zinc stearate are added together into a high-speed mixer and blended at a speed of 1200r / min for 10 minutes to obtain a mixture; the obtained mixture is blended, extruded, and granulated through a screw extruder at 170°C to 200°C to serve as an outer sheath layer masterbatch.
[0052] Cable preparation:
[0053] After conventional insulation masterbatch is melted in an extruder, it is extruded on the outer surface of the conductor core, and after cooling, an insulation layer tightly wrapped on the conductor core is formed; a shielding layer is woven on the outer surface of the insulation layer; the outer sheath masterbatch prepared in this comparative example is melted and extruded on the surface of the insulation shielding core at 170℃~200℃ in an extruder, and after cooling, an outer sheath layer tightly wrapped around the insulation shielding core is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.
[0054] Comparative Example 2
[0055] Modification of thermal conductive carbon fiber:
[0056] The cross-linking agent adsorption modification was not performed on the thermal conductive carbon fiber (in the subsequent processing and preparation of the outer sheath layer masterbatch, the cross-linking agent was added separately to the high-speed mixer for mixing), and the remaining operations were the same as in Example 1:
[0057] (1) Same as step (1) of Example 1;
[0058] (2) Same as step (2) of Example 1.
[0059] Processing and preparation of outer sheath layer masterbatch:
[0060] Calculated by weight, 100 parts of polypropylene, 10 parts of POE thermoplastic elastomer, 2.5 parts of the surface grafted modified thermal conductive carbon fiber prepared in this comparative example, 2 parts of dioctyl phthalate, 0.5 parts of antioxidant 1010, and 0.5 parts of zinc stearate are added together into a high-speed mixer and blended at a speed of 1200r / min for 10 minutes. During the blending process, 37.5 parts by weight of an acetone dispersion of diisopropyl peroxide with a mass concentration of 3% is sprayed into the mixture by a spray method; the resulting mixture is blended, extruded, and granulated at 170°C to 200°C through a screw extruder to serve as an outer sheath layer masterbatch.
[0061] Cable preparation:
[0062] After conventional insulation masterbatch is melted in an extruder, it is extruded on the outer surface of the conductor core, and after cooling, an insulation layer tightly wrapped on the conductor core is formed; a shielding layer is woven on the outer surface of the insulation layer; the outer sheath masterbatch prepared in this comparative example is melted and extruded on the surface of the insulation shielding core at 170℃~200℃ in an extruder, and after cooling, an outer sheath layer tightly wrapped around the insulation shielding core is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.
[0063] The outer sheath layer (or material) of the cable processed in the above embodiments and comparative embodiments was tested for thermal conductivity according to GB / T3139-2005 standard (the outer sheath layer masterbatch was melt-extruded at 170℃~200℃ to form a flat plate with a thickness of 5mm according to the extrusion process of the outer sheath layer in the above embodiments or comparative embodiments, and then the thermal conductivity test was performed on the instrument); the mechanical properties were tested according to GB / T 2951 "General Test Methods for Insulation and Sheath Materials of Electric and Optical Cables". The specific test results are shown in Table 1 (three samples were tested for the same item and the average was taken).
[0064] Table 1
[0065]
[0066] From the above table, when compared with Example 1, since the other end of the modified silane coupling agent grafted on the carbon fiber is a non-reactive group, the thermally conductive carbon fibers cannot be chemically connected together through a polymerization reaction, resulting in the thermally conductive carbon fibers being only close to each other in position but not having substantial connection and contact. Therefore, the thermal conductivity of the entire carbon fiber network is not as good as that of Example 1.
[0067] When compared with Example 1, since the cross-linking agent was not adsorbed on the heat-conducting carbon fiber in advance, the free radicals formed by the cross-linking agent were freely dispersed in the entire mixed system when the temperature was raised and extruded, instead of staying effectively on the carbon fiber, resulting in the initiation reaction stage. The carbon fibers in the system lacked effective mutual attraction, and finally in the carbon fiber network structure formed in the sheath coating layer matrix, the carbon fibers were more close to each other in position, but not substantially connected together, which ultimately affected the overall thermal conductivity. In Example 1, after the cross-linking agent was adsorbed on the carbon fiber through the modification step of this scheme, the cross-linking agent that did not separate from the carbon fiber was directly converted into free radicals on the carbon fiber after being heated. The free radical quenching effect between the free radicals of different carbon fibers enhanced the mutual attraction between the two carbon fibers, so that the probability of the local segments between the two carbon fibers being directly added together through the carbon-carbon double bond reaction was greatly increased. By analogy, in the entire heat-conducting carbon fiber network formed, the contact between the single carbon fiber and the carbon fiber became closer, making the heat conduction of the entire heat-conducting carbon fiber network faster and more effective.
[0068] At the same time, from the comparison of mechanical properties, it can be seen that although Example 1 concentrates the cross-linking agent on the thermally conductive carbon fiber in advance, the test piece produced by the processing reaction has only a slight decrease in mechanical strength compared to Comparative Example 2 in which the cross-linking agent is fully dispersed during mixing, and does not affect the use of the material. This is because the cross-linking agent is only physically adsorbed on the carbon fiber. Under the strong shearing effect of the extrusion temperature increase, a large part of the cross-linking agent adsorbed on the fiber will be separated from the fiber again and dispersed into the polypropylene base material, so the mechanical properties are still ensured; and the small part of the cross-linking agent that remains on the carbon fiber, as mentioned above, is directly converted into active free radicals on the carbon fiber, which is sufficient to effectively improve the mutual attraction between different carbon fibers.
Claims
1. A multilayer cable with high thermal conductivity, characterized in that: The cable comprises an insulated shielded wire core (1), wherein the insulated shielded wire core (1) comprises a conductor wire core (11), an insulating layer (12) tightly wrapped around the conductor wire core (11), and a shielding layer (13) tightly wrapped around the insulating layer (12); the cable further comprises an outer sheath layer (2) tightly wrapped around the insulated shielded wire core (1). Wherein, the outer sheath layer (2) is dispersedly doped with modified thermally conductive carbon fibers.
2. The multilayer cable with high thermal conductivity as claimed in claim 1, characterized in that: The conductor core (11) is formed by twisting a plurality of round copper wires.
3. The multi-layer structure cable with high thermal conductivity as claimed in claim 1, characterized in that: The shielding layer (13) is a wire mesh woven from copper wires.
4. The multi-layer structure cable with high thermal conductivity as claimed in claim 1, characterized in that: The outer sheath layer (2) comprises, by weight, 100 parts of polypropylene, 5 to 20 parts of POE thermoplastic elastomer, 1 to 3 parts of the modified thermally conductive carbon fiber, 2 to 3 parts of a plasticizer, 0.5 to 1.5 parts of an antioxidant, and 0.3 to 1 part of a lubricant.
5. The multi-layer structure cable with high thermal conductivity as claimed in claim 1 or 4, characterized in that: The modified thermally conductive carbon fiber is a thermally conductive carbon fiber that has been subjected to grafting modification by a reactive silane coupling agent and adsorption modification by a crosslinking agent in sequence. The preparation method of the modified thermally conductive carbon fiber is as follows: (1) immersing the thermally conductive carbon fiber in a hydrogen peroxide aqueous solution to achieve surface oxidation treatment of the thermally conductive carbon fiber, (2) immersing the thermally conductive carbon fiber that has been subjected to surface oxidation treatment in step (1) in a dispersion of the reactive silane coupling agent to achieve surface grafting modification of the thermally conductive carbon fiber, (3) immersing the thermally conductive carbon fiber that has been surface-grafted in step (2) in a dispersion of the crosslinking agent to achieve crosslinking agent adsorption modification of the thermally conductive carbon fiber. Wherein, the reactive silane coupling agent is a silane coupling agent with a carbon-carbon double bond in its molecular structure, and the cross-linking agent is an organic peroxide.
6. The multi-layer structure cable with high thermal conductivity as claimed in claim 5, characterized in that: In step (1), the thermally conductive carbon fiber is immersed in the hydrogen peroxide aqueous solution with a mass concentration of 3% to 5% for 1 to 5 hours according to a material-liquid ratio of 1:50 to 1:
10.
7. The multi-layer structure cable with high thermal conductivity as claimed in claim 5, characterized in that: In step (2), the thermally conductive carbon fiber subjected to surface oxidation treatment in step (1) is immersed in a dispersion of the reactive silane coupling agent having a mass concentration of 0.5% to 1.5% at a material-liquid ratio of 1:30 to 1:10 for 0.5 to 1.5 hours.
8. The multi-layer structure cable with high thermal conductivity as claimed in claim 5, characterized in that: In step (3), the thermally conductive carbon fiber surface-grafted in step (2) is immersed in a dispersion of the cross-linking agent having a mass concentration of 1% to 5% for 2 to 4 hours at a material-liquid ratio of 1:15 to 1:
10.
9. The multi-layer structure cable with high thermal conductivity as claimed in claim 1, characterized in that: The processing method of the cable comprises: melting the insulating layer masterbatch in an extruder, extruding it onto the outer surface of the conductor core (11), and cooling to form the insulating layer (12) tightly wrapped on the conductor core (11); weaving the shielding layer (13) on the outer surface of the insulating layer (12); and melting the masterbatch for preparing the outer sheath layer (2) in an extruder, extruding it onto the insulating shielding core (1), and cooling to form the outer sheath layer (2) tightly wrapped on the insulating shielding core (1).
Citation Information
Cited By
Preparation method of new energy automobile data connection wire harness
CN120663502A
A preparation method of a new energy vehicle data connection wire harness
CN120663502B